The Design and Development of Augmented Reality (AR) Application for Internet Evolution Learning Topics - Suhaizal, Hashim; Abdul Rahman, Khairul Anuar; Khamis, Nurhani; Shukor, Ummi Hanani; Che Lah, Noor Hidayah; Zulkifli, Nurul Nadwa (2023)
—The education field has seen numerous revolutions and innovations that have altered the teaching and learning process through the emergencen of Information and Communications Technology (ICT) which provides numerous benefits to both educators and students. However, there is concern that students' focus in the classroom becomes less due to the lack of pleasurable during the teaching and learning sessions. Thus, the existence of learning using Augmented Reality (AR) applications seems to help students improve their thinking skills in terms of cognitive as well as behaviorism. Therefore, this study proposed the Design and Development of an Augmented Reality (AR) Application for Internet Evolution Learning Topics known as AREvo. The methodology used in this study was based on design and development research (DDR) and ADDIE Model was used for designing and developing AREvo. Several platforms and software were used to develop AREvo. Several experts in the Creative Multimedia field from higher education were appointed to evaluate the AREvo in terms of its functionality, content design, interaction design, and presentation. The data analyze and obtained is in the form of frequency and feedback. Results revealed that the AREvo application can be used as additional material for instructors as well as students who are taking basic ICT courses. In addition, AREvo is expected to provide a positive impact in terms of functionality and usability of this AR application in the present and the future.